Exogenous melatonin improves Malus resistance to Marssonina apple blotch. Issue 4 (28th January 2013) - Yin, Lihua; Wang, Ping; Li, Mingjun; Ke, Xiwang; Li, Cuiying; Liang, Dong; Wu, Shan; Ma, Xinli; Li, Chao; Zou, Yangjun; Ma, Fengwang
Abstract: We examined whether exogenously applied melatonin could improve resistance to Marssonina apple blotch ( Diplocarpon mali ) by apple [ Malus prunifolia (Willd.) Borkh. cv. Donghongguo]. This serious disease leads to premature defoliation in the main regions of apple production. When plants were pretreated with melatonin, resistance was increased in the leaves. We investigated the potential roles for melatonin in modulating levels of hydrogen peroxide (H2 O2 ), as well the activities of antioxidant enzymes and pathogenesis‐related proteins during these plant–pathogen interactions. Pretreatment enabled plants to maintain intracellular H2 O2 concentrations at steady‐state levels and enhance the activities of plant defence‐related enzymes, possibly improving disease resistance. Because melatonin is safe and beneficial to animals and humans, exogenous pretreatment might represent a promising cultivation strategy to protect plants against this pathogen infection.